Environment-friendly single-component flame-retardant high-elasticity sealant and preparation method thereof

By using prefabricated silicone compositions and modified glass microbeads in silicone sealants, the problems of increased sealant density, poor construction performance and adhesive stability in the prior art are solved, and sealant products with high elasticity, flame retardant and economical benefits are achieved.

CN119614145APending Publication Date: 2025-03-14GUANGZHOU BAIYUN CHEM IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937968.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While the existing silicone sealant meets the flame retardant requirements of UL94 V-0, the density is increased and the filler and base glue are not easily compatible, which affects the construction performance and bonding stability. The increase in flame retardant filler leads to large changes in the mechanical properties of the sealant, low elongation and high brittleness.

Method used

Prefabricated silica gel compositions, including α,ω-dihydroxypolydimethylsiloxane, inorganic fillers, plasticizers and modified glass microbeads, are used to form a mixture system with synergistic flame retardant efficiency through dispersion stirring and modification treatment, to reduce the amount of flame retardant fillers and reduce the specific gravity of the sealant.

Benefits of technology

It realizes the low density, good mechanical strength, good extrusion, high elastic expansion, excellent flame retardant and adhesive properties of silicone sealant, meets the UL94 V-0 flame retardant requirements, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211948230000021
    Figure BDA0005211948230000021
  • Figure BDA0005211948230000031
    Figure BDA0005211948230000031
  • Figure BDA0005211948230000111
    Figure BDA0005211948230000111
Patent Text Reader

Abstract

The invention belongs to the technical field of silicone sealants, and particularly discloses an environment-friendly single-component flame-retardant high-elasticity sealant and a preparation method thereof. The environment-friendly single-component flame-retardant high-elasticity sealant provided by the invention comprises the following components in parts by mass: 50 parts of alpha, omega-dihydroxy polydimethylsiloxane; 30-60 parts of activated calcium carbonate; 30 to 80 parts of a prefabricated silica gel composition; 4-10 parts of a cross-linking agent; 2-8 parts of a catalyst; and 0.2 to 2 parts of a coupling agent. The environment-friendly single-component flame-retardant high-elasticity sealant provided by the invention has the advantages of relatively low density, good mechanical strength, good extrudability, high elastic expansion and contraction rate and excellent flame-retardant and adhesive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone sealants, and in particular to an environmentally friendly, single-component flame-retardant high-elastic sealant and a preparation method thereof. Background Art

[0002] Silicone sealant is a paste adhesive made of polydimethylsiloxane as the main raw material, supplemented by cross-linking agent, filler, plasticizer, coupling agent, and catalyst mixed under vacuum. It solidifies to form elastic silicone rubber by reacting with water vapor in the air at room temperature. The silicone sealant body has excellent weather resistance, heat resistance, high and low temperature resistance, good chemical stability and good insulation properties. In addition, its wide applicability can achieve the bonding and adhesion between most industrial materials, with high efficiency and stability. According to the different fillers and additives selected, silicone sealant products can have different special properties such as thermal conductivity, flame retardancy, electrical conductivity, high temperature resistance, mildew resistance, etc. It shines in many industries.

[0003] Among them, the electronic and electrical industry, with its development and environmental protection requirements, has stricter requirements for certain silicone sealants. First of all, some household appliances require UL94 V-0 flame retardant requirements, and environmental protection requirements are sulfur-free and halogen-free. At the same time, the sealant is required to have a lower density requirement in order to pursue lightweight products and higher extrudability construction conditions, in order to pursue the needs of continuous and rapid production. At present, the common types of flame retardants, halogen flame retardants obviously do not meet the requirements of industry environmental protection regulations; inorganic flame retardants have the advantages of chemical stability, wide sources, and low prices. However, using inorganic flame retardants as fillers and filling them in large quantities in silicone sealants increases the density of sealant products, and the fillers and base glue systems are not easy to be compatible and separate, and the large amount of added inorganic fillers seriously affects the construction performance and long-term bonding stability of the product. At the same time, flame-retardant silicone sealants are required to have good mechanical properties and elastic expansion and contraction of normal sealants in certain occasions. Ordinary silicone sealants on the market are easy to burn when exposed to open flames and are difficult to extinguish themselves. Flame-retardant sealants generally need to add a large amount of flame-retardant fillers to have flame-retardant properties, but in fact a large amount of flame-retardant fillers makes the mechanical properties of the sealant vary greatly. For example, its elongation becomes extremely low and very brittle. Summary of the invention

[0004] In view of the above-mentioned shortcomings, the present invention provides an environmentally friendly, one-component flame-retardant high-elastic sealant and a preparation method thereof. The sealant of the present invention has low density, good mechanical strength, good extrudability, high elasticity, excellent flame retardancy and bonding properties.

[0005] In order to achieve the above object, the present invention provides a prefabricated silica gel composition, which comprises, by weight:

[0006]

[0007] The preparation method of the prefabricated silica gel composition comprises the following steps:

[0008] 50 parts of α, ω-dihydroxy polydimethylsiloxane, 20-50 parts of inorganic filler and 1-10 parts of plasticizer are added into a planetary machine, the dispersion speed is 1000-1500 rpm, and the vacuum degree reaches 0.085-0.095 MPa. Start dispersing and stirring for 60-120 minutes, and then add 5-20 parts of modified glass microbeads and 0.1-1 part of plasticizer in batches, respectively, at a dispersion speed of 400-800 rpm. After continuing stirring for 120-300 minutes, a prefabricated silica gel composition is obtained for standby use.

[0009] According to one aspect of the present invention, the viscosity of the α, ω-dihydroxy polydimethylsiloxane is 1000-20000 cps; the inorganic filler is at least one of melamine phosphate, aluminum hydroxide, magnesium hydroxide, magnesium carbonate, zinc borate, montmorillonite, and talc; and the plasticizer is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and polyether silicone oil.

[0010] According to one aspect of the present invention, the modified glass microspheres are obtained by surface-treating ordinary hollow glass microspheres with a modifier; wherein the modified glass microspheres are hollow thin-walled spherical structures with a particle size of 10 to 30 μm, a wall thickness of about 1 to 2 μm, and a density of 0.2 to 0.3 g / cm 3 .

[0011] According to one aspect of the present invention, the preparation method of the modified glass microspheres is as follows: ordinary hollow glass microspheres are placed in a solvent and stirred until dispersed, and stirred at 60-90°C and 300-800rpm, a modifier is slowly added, and the stirring reaction is continued for 3-5h; then, a vacuum is slowly drawn, and a constant temperature of 50-60°C is maintained while continuing to stir and separate the solvent to obtain modified glass microspheres, which are dried for later use; wherein the solvent is at least one of dichloromethane, alcohol, acetone, ethyl acetate or butyl acetate; and the modifier is at least one of dodecyldimethylbenzylammonium bromide, γ-aminopropyltriethoxysilane, and bis-(trimethoxysilylpropyl)amine.

[0012] It should be noted that the main component of the modified glass microspheres is borosilicate.

[0013] Based on the same inventive concept, the present invention also provides an environmentally friendly, one-component flame-retardant, high-elasticity sealant, which comprises, by weight:

[0014]

[0015]

[0016] Wherein, the prefabricated silica gel composition is the prefabricated silica gel composition according to any one of claims 1 to 4.

[0017] According to one aspect of the present invention, the viscosity of the α,ω-dihydroxy polydimethylsiloxane is 1000-100000 cps. Preferably, the viscosity of the α,ω-dihydroxy polydimethylsiloxane is 10000-50000 cps.

[0018] According to one aspect of the present invention, the amount of the activated calcium carbonate added is greater than the amount of the inorganic filler added.

[0019] According to one aspect of the present invention, the activated calcium carbonate is nano calcium carbonate modified by zinc stearate; wherein the particle size of the activated calcium carbonate is 25 to 40 nm, and the specific surface area is 15 to 30 m 2 / g.

[0020] It should be noted that the above-mentioned active calcium carbonate powder has the best reinforcing effect and can more effectively improve the overall comprehensive stability of the silicone sealant.

[0021] It should be noted that controlling the addition ratio and surface particle size of activated calcium carbonate and inorganic filler can form a more stable compatible system with the silicone rubber system, which is more conducive to uniform mixing with other additives during the processing process, making the prepared silicone sealant colloid more stable and with better performance.

[0022] According to one aspect of the present invention, the cross-linking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, methyl silicate, and ethyl silicate; the catalyst is at least one of isopropyl titanate, isobutyl titanate, and tetra-tert-butyl titanate complex; the coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane.

[0023] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned environmentally friendly, one-component flame-retardant and highly elastic sealant, comprising the following steps:

[0024] Add α,ω-dihydroxypolydimethylsiloxane and activated calcium carbonate into a disperser, dehydrate and stir for 120 minutes at a temperature of 100-150°C, a vacuum degree of 0.085-0.095MPa, and a rotation speed of 1000-3000rpm, cool to below 30°C, reduce the stirring speed to 300-800rpm, slowly add the prefabricated silica gel composition, and continue stirring for 60 minutes; then, under a vacuum degree of 0.085-0.095MPa, add a crosslinking agent, a catalyst, and a coupling agent in turn, stir and disperse until the reaction is complete.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention uses α, ω-dihydroxy polydimethylsiloxane based glue and commonly used inorganic fillers, melamine phosphate and other components, firstly modifies the surface of glass microspheres, and then pre-produces a silica gel composition with special functions through process production. The above process treatment can not only improve the compatibility of each original component, but also reduce the relative density of the finished product. The modified glass microspheres of the present invention have certain flame retardancy, and they are processed with nano calcium carbonate fillers, melamine phosphate and inorganic fillers in the sealant system to form a new mixture system, which can improve the overall synergistic flame retardancy. Under the same flame retardancy requirements, the amount of flame retardant filler added is also reduced, the specific gravity of silane sealant is reduced, and the adhesion of the sealant product to the substrate, as well as the strength and tensile elasticity after curing are greatly improved. At the same time, it has both good construction performance and large extrudability requirements, which greatly meets the production needs of customers and has low production costs.

[0027] (2) Compared with the existing sealants, the one-component flame retardant sealant of the present invention can greatly reduce the amount of inorganic filler added while meeting the flame retardant requirements of UL94 V-0 level. At the same time, it has a more long-lasting and effective bonding stability for most common materials, such as aluminum, glass, stainless steel, PC, etc., making the product lighter, with higher extrudability and thixotropy, convenient for on-site construction conditions, and has stable and good economic benefits. DETAILED DESCRIPTION

[0028] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0029] Example 1

[0030] A method for preparing an environmentally friendly, one-component flame-retardant, high-elasticity sealant comprises the following steps:

[0031] (1) Preparation of modified glass microspheres: particle size is 25 μm, wall thickness is about 1 μm, density is 0.24 g / cm 3 Add 20 parts of glass microspheres into 120 parts of dichloromethane and disperse and stir, then add 6 parts of dodecyldimethylbenzyl ammonium bromide and 4 parts of γ-aminopropyltriethoxysilane, stir for 120 minutes at 80°C and 400rpm, then continue to slowly evacuate, maintain a constant temperature of 60°C and continue stirring to separate the solvent, dry, and obtain modified glass microspheres for standby use.

[0032] (2) Preparation of prefabricated silica gel composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500cps at room temperature, 30 parts of melamine phosphate, and 5 parts of polyether modified silicone oil were added to a planetary machine, the dispersion speed was 1500rpm, the vacuum degree reached below 0.090MPa, and the dispersion stirring was started for 60min. Then, 20 parts of modified glass microbeads and 0.5 parts of hexadecyltrimethoxysilane were added three times in equal parts, the dispersion speed was 500rpm, and the stirring was continued for 120min to obtain a composite prefabricated silica gel composition for standby use.

[0033] (3) Preparation of base material: 50 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser, dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30°C to obtain a base material for standby use.

[0034] (4) Preparation of silicone sealant (environmentally friendly, one-component flame-retardant, high-elasticity sealant): Add the prefabricated silicone composition prepared in (2) to the base material prepared in (3) and mix them. Stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, a mixed catalyst of 3 parts of isopropyl titanate chelate, and a mixed coupling agent of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0035] Example 2

[0036] A method for preparing an environmentally friendly, one-component flame-retardant, high-elasticity sealant comprises the following steps:

[0037] (1) Preparation of modified glass microspheres: The particle size is 25 μm, the wall thickness is about 1 μm, and the density is 0.27 g / cm 3 Add 15 parts of glass microspheres into 100 parts of dichloromethane and disperse and stir, then add 6 parts of dodecyldimethylbenzyl ammonium bromide and 4 parts of γ-aminopropyltriethoxysilane, stir for 120 minutes at 80°C and 400rpm, then continue to slowly evacuate, maintain a constant temperature of 60°C and continue stirring to separate the solvent, dry, and obtain modified glass microspheres for standby use.

[0038] (2) Preparation of prefabricated silica gel composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500cps at room temperature, 45 parts of melamine phosphate, and 4 parts of polyether modified silicone oil are added to a planetary machine, the dispersion speed is 1500rpm, the vacuum degree reaches below 0.090MPa, and the dispersion stirring is started for 60h. Then, 15 parts of modified glass microbeads and 0.4 parts of hexadecyltrimethoxysilane are added three times in equal parts, the dispersion speed is 500rpm, and the stirring is continued for 120min to obtain a composite prefabricated silica gel composition for standby use.

[0039] (3) Preparation of base material: 50 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser, dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30°C to obtain a base material for standby use.

[0040] (4) Preparation of silicone sealant (environmentally friendly, one-component flame-retardant, high-elasticity sealant): Add the prefabricated silicone composition prepared in (2) to the base material prepared in (3), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane, and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0041] Example 3

[0042] A method for preparing an environmentally friendly, one-component flame-retardant, high-elasticity sealant comprises the following steps:

[0043] (1) Preparation of modified glass microspheres: The particle size is 25 μm, the wall thickness is about 1 μm, and the density is 0.27 g / cm 3 10 parts of glass microspheres were added to 80 parts of dichloromethane and dispersed and stirred, and then 4 parts of dodecyldimethylbenzyl ammonium bromide and 3 parts of γ-aminopropyltriethoxysilane were added, and stirred at 80°C and 400rpm for 120min, and then slowly evacuated, maintained at a constant temperature of 60°C, and continued to stir to separate the solvent, and dried to obtain modified glass microspheres.

[0044] (2) Preparation of prefabricated silica gel composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500cps at room temperature, 50 parts of melamine phosphate, and 5 parts of polyether modified silicone oil were added to a planetary machine, the dispersion speed was 1500rpm, the vacuum degree reached below 0.090MPa, and the dispersion stirring was started for 60h. Then, 10 parts of modified glass microbeads and 0.4 parts of hexadecyltrimethoxysilane were added three times in equal parts, the dispersion speed was 500rpm, and the stirring was continued for 120min to obtain a composite prefabricated silica gel composition for standby use.

[0045] (3) Base material preparation: 50 parts of α,ω-dihydroxy polysiloxane with a viscosity of 25000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 40 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser, dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30°C to obtain a base material for standby use.

[0046] (4) Preparation of silicone sealant (environmentally friendly, one-component flame-retardant, high-elasticity sealant): Add the prefabricated silicone composition prepared in (2) to the base material prepared in (3), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane, and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0047] Example 4

[0048] A method for preparing an environmentally friendly, one-component flame-retardant, high-elasticity sealant comprises the following steps:

[0049] (1) Preparation of modified glass microspheres: The particle size is 25 μm, the wall thickness is about 1 μm, and the density is 0.27 g / cm 3 10 parts of glass microspheres were added to 60 parts of dichloromethane and dispersed and stirred, and then 3 parts of dodecyldimethylbenzyl ammonium bromide and 2 parts of γ-aminopropyltriethoxysilane were added, and stirred at 80°C and 400rpm for 120min, and then vacuumed slowly, maintained at a constant temperature of 60°C, and continued to stir to separate the solvent, and dried to obtain modified glass microspheres.

[0050] (2) Preparation of silicone composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 cps at room temperature, 40 parts of melamine phosphate, and 5 parts of polyether modified silicone oil were added to a planetary machine, the dispersion speed was 1500 rpm, the vacuum degree reached below 0.090 MPa, and the dispersion stirring was started for 60 hours. Then, 10 parts of modified glass microbeads and 0.4 parts of hexadecyltrimethoxysilane were added three times in equal parts, the dispersion speed was 500 rpm, and the stirring was continued for 120 minutes to obtain a composite silicone composition for standby use.

[0051] (3) Base material preparation: 50 parts of α,ω-dihydroxy polysiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser, dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30°C to obtain a base material for standby use.

[0052] (4) Preparation of silicone sealant: Add the prefabricated silicone composition prepared in (2) to the base material prepared in (3), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent composed of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0053] Comparative Example 1

[0054] The difference between this comparative example and the embodiment is that the glass microspheres are not modified.

[0055] (1) Preparation of silicone composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 cps at room temperature, 30 parts of melamine phosphate, and 5 parts of polyether modified silicone oil were added to a planetary machine, and the dispersion speed was 1500 rpm. Under the condition that the vacuum degree reached 0.085-0.095 MPa, dispersion stirring was started for 60 hours, and then 20 parts of glass microbeads and 0.4 parts of hexadecyltrimethoxysilane were added three times in equal parts, and the dispersion speed was 500 rpm. After stirring for 120 minutes, a composite silicone composition was obtained for standby use.

[0056] (2) Base material preparation: 50 parts of α,ω-dihydroxy polysiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a planetary mill and dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa and a rotation speed of 2500 rpm. After cooling, the base material was obtained for standby use.

[0057] (3) Preparation of silicone sealant: Add the silicone composition prepared in (1) to the base material prepared in (2), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent composed of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0058] Comparative Example 2

[0059] The difference between this comparative example and the example is that the prefabricated silica gel composition is not prepared, but the raw materials are directly added.

[0060] (1) Preparation of modified glass microspheres: particle size is 25 μm, wall thickness is about 1 μm, density is 0.27 g / cm 3 20 parts of glass microspheres were added to 120 parts of dichloromethane and dispersed and stirred, and then 6 parts of dodecyldimethylbenzyl ammonium bromide and 4 parts of γ-aminopropyltriethoxysilane were added, and stirred at 80°C and 400rpm for 120min, and then vacuumed slowly, maintained at a constant temperature of 60°C, and continued to stir to separate the solvent, and dried to obtain modified glass microspheres.

[0061] (2) Base material preparation: 50 parts of α,ω-dihydroxy polysiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser, dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30°C to obtain a base material for standby use.

[0062] (3) Preparation of silicone sealant: To the base material prepared in (2), 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 cps at room temperature, 30 parts of melamine phosphate, 5 parts of polyether modified silicone oil, 20 parts of modified glass microspheres and 0.5 parts of hexadecyltrimethoxysilane were added and mixed separately in a planetary mixer. The mixture was stirred for 60 minutes at a dispersion speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, a mixed crosslinking agent of 2 parts of vinyltrimethoxysilane and 4 parts of methyltrimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent of 0.3 parts of γ-aminopropyltrimethoxysilane, 0.3 parts of γ-glycidoxypropyltrimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyltrimethoxysilane were added. Continue stirring at a speed of 1200prm, with the vacuum degree reaching below 0.090MPa, disperse for 60 minutes, and then discharge and bottle.

[0063] Comparative Example 3

[0064] The difference between this comparative example and the embodiment is that no modified glass microbeads are added to the prefabricated silica gel composition.

[0065] (1) Preparation of silicone composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 cps at room temperature, 50 parts of melamine phosphate, and 8 parts of polyether modified silicone oil were added to a planetary machine, the dispersion speed was 1500 rpm, the vacuum degree reached below 0.090 MPa, and the dispersion stirring was started for 60 minutes. Then, 0.5 parts of hexadecyltrimethoxysilane was added, and the dispersion speed was continued at 500 rpm. After stirring for 120 minutes, a composite silicone composition was obtained and set aside.

[0066] (2) Preparation of base material: 50 parts of α, ω-dihydroxy polysiloxane with a viscosity of 20,000 cps at room temperature and 50 parts of nano-activated calcium carbonate modified by zinc stearate with a particle size of 30 nm and a specific surface area of ​​25 m2 / g are added to a disperser, dehydrated and stirred for 120 minutes at a temperature of 120° C., a vacuum degree of 0.090 MPa, and a rotation speed of 2500 rpm, and then cooled to below 30° C. to obtain a base material for standby use.

[0067] (3) Preparation of silicone sealant: Add the silicone composition prepared in (1) to the base material prepared in (2), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent composed of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0068] Comparative Example 4

[0069] The difference between this comparative example and the embodiment is that no modified glass microbeads are added to the prefabricated silica gel composition, and flame retardant fillers are added.

[0070] (1) Preparation of silicone composition: 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 1500 cps at room temperature, 80 parts of melamine phosphate, and 8 parts of polyether modified silicone oil were added to a planetary machine, the dispersion speed was 1500 rpm, the vacuum degree reached below 0.090 MPa, and the dispersion stirring was started for 60 minutes. Then, 0.5 parts of hexadecyltrimethoxysilane was added, and the dispersion speed was continued at 500 rpm. After stirring for 120 minutes, a composite silicone composition was obtained for standby use.

[0071] (2) Base material preparation: 50 parts of α,ω-dihydroxy polysiloxane with a viscosity of 20,000 cps at room temperature, a particle size of 30 nm, and a specific surface area of ​​25 m 2 50 parts of nano-activated calcium carbonate modified by zinc stearate were added into a disperser and dehydrated and stirred for 120 minutes at a temperature of 120°C, a vacuum degree of 0.090 MPa and a rotation speed of 2500 rpm. After cooling, the base material was obtained for standby use.

[0072] (3) Preparation of silicone sealant: Add the silicone composition prepared in (1) to the base material prepared in (2), mix, and stir for 20 minutes at a dispersing speed of 1000 rpm and a vacuum degree of 0.090 MPa. Then, add a mixed crosslinking agent of 2 parts of vinyl trimethoxysilane and 4 parts of methyl trimethoxysilane, 3 parts of isopropyl titanate chelate mixed catalyst, and a mixed coupling agent composed of 0.3 parts of γ-aminopropyl trimethoxysilane, 0.3 parts of γ-glycidoxypropyl trimethoxysilane and 0.3 parts of β-(3,4-epoxycyclohexane)ethyl trimethoxysilane. Continue to disperse for 60 minutes at a stirring speed of 1200 rpm and a vacuum degree of less than 0.090 MPa, and then discharge and bottle.

[0073] Performance testing and result analysis:

[0074] The sealants prepared in Examples 1-4 and Comparative Examples 1-4 were tested for sealant density according to GB / T 13477.2-2018; their dielectric strength was tested according to GB / T 1695-2005; and the tensile strength and elongation at break of vulcanized rubber were tested according to GB / T528-2009. After the specimens were cured for 3 days at 23±2°C and 50±5%RH, they were aged at 280°C for 7 days, and then tensile tested for their high-temperature mechanical properties; the flame retardant grade test was tested according to the vertical burning test method classified as UL94V-0ULV-1ULV-2 by the material. The test results are shown in Table 1 below.

[0075] Table 1:

[0076]

[0077] As shown in Examples 1 to 4 of Table 1, the highly elastic, flame-retardant adhesive sealant of the present invention has low density, good mechanical strength, good extrudability, high elasticity, excellent flame retardant and adhesive properties. As shown in Table 1, without modified glass microspheres, the mechanical properties and extrudability of silicone sealant rapidly decrease, the density is higher, and the flame retardant properties of V-0 level cannot be achieved. As shown in Table 1, without modified glass microspheres, the amount of inorganic filler added in Comparative Example 4 is greatly increased, and the flame retardant properties of V-2 level can still only be achieved. It shows that the modified hollow glass microspheres prepared by the present invention can reduce the addition ratio of inorganic flame retardant fillers in the sealant system, improve the synergistic flame retardant efficiency of fillers, reduce the density of sealants, and improve the extrudability of sealants. As shown in Table 1, the process of preparing the components of the prefabricated silica gel composition is improperly processed, and it cannot be stably compatible with other filler components to form synergistic flame retardancy, and the comprehensive performance of other aspects is poor. In addition, from the comparison between Examples 1-4 and Comparative Examples 1-3 in Table 1, it can be seen that there is no significant difference in the dielectric strength of the silicone sealant, indicating that the addition of modified glass microspheres does not have much effect on the dielectric properties of the silicone sealant, so the silicone sealant of the present invention has excellent insulation performance.

[0078] In summary, the modified glass microspheres and prefabricated silica gel composition of the present invention cooperate with the flame retardant filler, and within a certain ratio, the silicone sealant of the present invention has a relatively low density, good mechanical strength, good extrudability, high elasticity, excellent flame retardant and adhesive properties. At the same time, the silicone sealant of the present invention has good economic benefits.

[0079] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A prefabricated silica gel composition, characterized in that: According to the mass percentage, it includes: The preparation method of the prefabricated silica gel composition comprises the following steps: 50 parts of α, ω-dihydroxy polydimethylsiloxane, 20-50 parts of inorganic filler and 1-10 parts of plasticizer are added into a planetary machine, the dispersion speed is 1000-1500 rpm, and the vacuum degree reaches 0.085-0.095 MPa. Start dispersing and stirring for 60-120 minutes, and then add 5-20 parts of modified glass microbeads and 0.1-1 part of plasticizer in batches, respectively, at a dispersion speed of 400-800 rpm. After continuing stirring for 120-300 minutes, a prefabricated silica gel composition is obtained for standby use.

2. The prefabricated silica gel composition according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane is 1000-20000cps; the inorganic filler is at least one of melamine phosphate, aluminum hydroxide, magnesium hydroxide, magnesium carbonate, zinc borate, montmorillonite and talc; the plasticizer is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane and polyether silicone oil.

3. The prefabricated silica gel composition according to claim 1, characterized in that: The modified glass microspheres are obtained by surface-treating ordinary hollow glass microspheres with a modifier; wherein the modified glass microspheres are hollow thin-walled spherical structures with a particle size of 10 to 30 μm, a wall thickness of about 1 to 2 μm, and a density of 0.2 to 0.3 g / cm 3 .

4. The prefabricated silica gel composition according to claim 3, characterized in that: The preparation method of the modified glass microspheres is as follows: ordinary hollow glass microspheres are placed in a solvent and stirred until dispersed, and stirred at 60-90° C. and 300-800 rpm, a modifier is slowly added, and the stirring reaction is continued for 3-5 hours; then, vacuuming is slowly started, and the solvent is separated by stirring at a constant temperature of 50-60° C. to obtain modified glass microspheres, which are dried for later use; wherein the solvent is at least one of dichloromethane, alcohol, acetone, ethyl acetate or butyl acetate; and the modifier is at least one of dodecyldimethylbenzylammonium bromide, γ-aminopropyltriethoxysilane, and bis-(trimethoxysilylpropyl)amine.

5. An environmentally friendly, one-component flame-retardant, highly elastic sealant, characterized in that: According to the mass percentage, it includes: Wherein, the prefabricated silica gel composition is the prefabricated silica gel composition according to any one of claims 1 to 4.

6. The environmentally friendly, one-component flame-retardant, highly elastic sealant according to claim 5, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane is 1000-100000 cps.

7. The environmentally friendly, one-component flame-retardant, highly elastic sealant according to claim 5, characterized in that: The added amount of the active calcium carbonate is greater than the added amount of the inorganic filler.

8. The environmentally friendly, one-component flame-retardant, highly elastic sealant according to claim 5, characterized in that: The active calcium carbonate is obtained by modifying nano calcium carbonate with zinc stearate; wherein the particle size of the active calcium carbonate is 25-40 nm, and the specific surface area is 15-30 m 2 / g.

9. The environmentally friendly, one-component flame-retardant, highly elastic sealant according to claim 5, characterized in that: The crosslinking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, methyl silicate, and ethyl silicate; the catalyst is at least one of isopropyl titanate, isobutyl titanate, and tetra-tert-butyl titanate complex; the coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and β-(3,4-epoxycyclohexane)ethyltrimethoxysilane.

10. The method for preparing the environmentally friendly, one-component flame-retardant and highly elastic sealant according to claim 5, characterized in that: The following steps are involved: Add α,ω-dihydroxypolydimethylsiloxane and activated calcium carbonate into a disperser, dehydrate and stir for 120 minutes at a temperature of 100-150°C, a vacuum degree of 0.085-0.095MPa, and a rotation speed of 1000-3000rpm, cool to below 30°C, reduce the stirring speed to 300-800rpm, slowly add the prefabricated silica gel composition, and continue stirring for 60 minutes; then, under a vacuum degree of 0.085-0.095MPa, add a crosslinking agent, a catalyst, and a coupling agent in turn, stir and disperse until the reaction is complete.